Expatriates, Rise of Telecommuting and Implications for International Business - Arslan, Ahmad; Gölgeci, Ismail; Larimo, Jorma (Routledge, 2020)
International business (IB) travel has long been considered an important aspect of international business management strategies of multinational enterprises (MNEs). Extant literature further recognizes that expatriate managers are an essential cornerstone of MNEs’ global strategies. They play a crucial role in the management of subsidiaries as well as in knowledge transfer of organizational routines and practices. Covid-19 has caused a collapse of the airline industry due to travel restrictions, which have been referred to remain in place in one way or another for the foreseeable future. The issue of international travel has become a daunting problem in relation to Covid-19 pandemic. Many MNEs have been overwhelmed by the unprecedented and severe problems they face in regard to the mobility of their workforce. The fundamental changes in the way the global economy is being run, and firms operate offer profound future research opportunities on labor mobility and IB travel.
Keywords: IB Travel; Telecommuting; COVID-19; fi=Kansainvälinen liiketoiminta|en=International Business|